Client-consultant interaction: ‘outsider’ status and ambiguity - Skovgaard Smith, Irene (Henry Stewart Talks, 2015)
The industry and its relationship-building trend, The complexities and dynamics of interaction, Anthropological study of consulting in action, Dimensions of attributed "outsider" status